An early warning system for highly pathogenic viruses borne by waterbird species and related dynamics of climate change in the Caspian Sea region: Outlines of a concept - G. Petherbridge; A. A. Gadzhiev; А. М. Shestopalov; A. Yu. Alekseev; K. A. Sharshov; M. G. Daudova (Юг России: экология, развитие, 2022)
Aim. Formulation of the outlines of the concept of ViEW (Viral Early Warning) which is intended as a long term system of multidisciplinary transboundary cooperation between specialist institutions of all five Caspian region states to research, regularly monitor and share data about the generation, transmission and epidemiology of avian‐borne pathogens and their vectors in the region, and the ways climate change may affect these processes.Material and Methods. The concept is based on the multidisciplinary experience of the authors in researching the processes incorporated in the ViEW concept and on an in‐depth survey of the literature involved.Results. The outlines of the ViEW concept are presented in this study for review and comment by interested parties and stakeholders.Conclusion. Review of activities and opinions of specialists and organizations with remits relating to the development, establishment and maintenance of ViEW, indicates that such a system is a necessity for global animal and human health because of the role that the Caspian region plays in the mass migration of species of waterbird known as vectors for avian influenza and the already evident impacts of climate change on their phenologies. Waterbirds frequenting the Caspian Sea littorals and their habitats together constitute a major potential global hotspot or High Risk region for the generation and transmission of highly pathogenic avian influenza viruses and other dangerous zoonotic diseases.